No Social Recognition Needed? What Drives Entrepreneurial Intention Among Indonesian University Students - Santi Rimadias (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to identify the factors influencing entrepreneurial intentions among Indonesian university students Specifically, it examines the roles of personality traits, entrepreneurial training and education, social recognition, self-efficacy, and entrepreneurial attitudes. The research employs a quantitative approach using an online questionnaire distributed to 250 active students from the Faculty of Economics and Business across major Indonesian cities. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings suggest universities should enhance the effectiveness of entrepreneurship education and training programs by incorporating practical activities such as business simulations, mentoring, and incubators to foster positive attitudes and self-confidence among students. The study recommends that universities improve the quality and effectiveness of entrepreneurship education, while policymakers should support initiatives that encourage entrepreneurial development and promote positive social recognition of entrepreneurship as a viable and rewarding career path.